Strategi Komunikasi Digital untuk Meningkatkan Visibilitas UMKM Perempuan: Studi Kasus Kota Padang - weriframayeni, annisa; Sri Mona Octafia; Elsa Widia (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2025)
Women's participation in Indonesia's economy has long been a key focus, with over 60 percent of MSMEs managed by women. While digitalization and its impact on MSME performance in Padang City have been widely studied, research specifically addressing effective digital communication strategies remains limited. This study aims to provide comprehensive insights into effective digital communication approaches to enhance the marketing performance of women-owned MSMEs in Padang. The analysis focuses on the types of digital platforms used, the nature of messages conveyed, and patterns of interaction with customers through social media, websites, and e-commerce platforms. The methodology involves primary data collection through in-depth interviews and surveys, along with secondary data on MSME profiles. Data analysis employs multivariate regression to examine the influence of multiple independent variables on dependent variables simultaneously. The findings reveal that strategies involving social media and online advertising are particularly effective in boosting MSME visibility on digital platforms. Meanwhile, the use of websites combined with online advertisements is more effective in driving traffic to MSME websites.